Solar-driven phase change microencapsulation with efficient Ti4O7 nanoconverter for latent heat storage. (November 2018) - Zhang, Ying; Li, Xiaoyu; Li, Jianqiang; Ma, Chenyu; Guo, Lijiang; Meng, Xiangmin
Abstract: A sort of novel microencapsulated phase change materials (PCMs) has attracted much attention for energy storage. However, the solar energy utilization efficiency of traditional microcapsulated PCMs is still not very high up to date. In this work, new core@shell structured paraffin@SiO2 /Ti4 O7 composite microcapsules were developed to harvest environmental full-spectrum sunlight by smart and rational design using a sol-gel method. The SiO2 shell not only prevented the leakage of paraffine, but also improves its thermal conductivity. The black 300 nm Ti4 O7 particles, which were successfully embedded into the SiO2 shell, can achieve the efficient absorption of sunlight and simultaneously high conversion from light to thermal. The resultant paraffin@SiO2 /Ti4 O7 microcapsules retained most enthalpy of paraffin, increased its stability, and exhibited an excellent thermal energy storage performance. The thermal conductivity of paraffin@SiO2 /Ti4 O7 microcapsules was significantly enhanced by 334.87% (1.322 W m −1 K −1 ) compared with 0.304 W m −1 K −1 of one for paraffin. When the mass fraction of Ti4 O7 nanoparticles is 3 wt% of paraffin, these paraffin@SiO2 /Ti4 O7 microcapsules exhibited remarkable 85.36% of photo-thermal storage efficiency compared with 24.14% of one for paraffin. Due to their huge superiority of high efficient use of abundant solar energy in natural resources, these new photo-driven PCMs are very promising materials for solar-to-thermal conversion and energy storage. Graphical abstract: fx1 Highlights: The microcapsules with SiO2 shell modified by Ti4 O7 nanoparticles and paraffin core were fabricated successfully. The microcapsules exhibited remarkable photo-thermal conversion performance with photo-thermal storage efficiency of 85.36%. The SiO2 shell modified by Ti4 O7 nanoparticles greatly enhanced the microcapsules' thermal conductivity which is up to 1.322 W m −1 K −1 .